Python Data Cleaning Cookbook Modern Techniques and Python Tools to Detect and Remove Dirty Data and Extract Key Insights - Walker, Michael (Packt Publishing, Limited, 2020)
The book shows you how to view data from multiple perspectives, including data frame and column attributes. You will cover common and not-so-common challenges that are faced while cleaning messy data for complex situations. You will learn to manipulate data and get them down to a form that can be useful for making the right decisions.
Description based upon print version of record
Keywords: Analysis of variance; Database management; Data mining; Python (Computer program language); Analysis of Variance; Data Mining; Analyse de variance; Bases de données; Gestion; Exploration de données (Informatique); Python (Langage de programmation)